Effects of seepage velocity and concentration on chromium(VI) removal in abiotic and biotic iron columns. Issue 3 (18th March 2020) - Yin, Weizhao; Fang, Zhanqiang; Huang, Jingling; Li, Ping; Zhong, Jiawei; Chiang, Penchi; Wu, Jinhua
Abstract: Continuous‐flow iron and bio‐iron columns were used to evaluate the effects of seepage velocity and concentration on Cr(VI) removal from groundwater. Solid‐phase analysis showed that microorganisms accelerated iron corrosion by excreting extracellular polymeric substances and generated highly reactive minerals containing Fe(II), which gave the bio‐iron column a longer life span and enhanced capacity for Cr(VI) removal via enhanced adsorption and reduction by reactive minerals. The bio‐iron column showed much higher Cr(VI) removal capacity than the iron column with increasing Cr(VI) loading, which was obtained by increasing the seepage velocity or influent Cr(VI) concentration from 95 to 1138 m yr −1 and from 5 to 40 mg L −1, respectively. When the Cr(VI) loading varied in a range of 0 to 10 mg L −1 h −1, the bio‐iron column had a 60% longer longevity and one‐ to sixfold higher Cr(VI) elimination capacity than the iron column. This result indicated that, under fluctuating hydraulic conditions [e.g., seepage velocity and Cr(VI) concentration], the presence of microorganisms can significantly boost Cr(VI) removal using Fe 0 –based permeable reactive barriers.